Coupled superconductors and beyond - Josephson, Brian D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
This paper describes the events leading to the discovery of coupled superconductors, the author’s move in the 1970s to a perspective where mind plays a role comparable to matter, and the remarkable hostility sometimesencountered by those who venture into unconventional areas.